IMPLEMENTASI BENTUK-BENTUK LAYANAN BK OLEH GURU KELAS DI UPTD SD INPRES AMPERA - Ayu Y. Maro; Bendelina Alomau, Yessy Mata, Petrus Mau Tellu Dony, Yermia S. Wabang, Antonius A. Saetban (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to describe the implementation of guidance and counseling (BK) services by classroom teachers in elementary schools, specifically at the UPTD SD Inpres Ampera, Alor Barat Laut District. The background of this study is based on the important role of BK services in supporting the personal, social, academic, and career development of students, especially at the elementary level. Amidst the limited number of professional counselors in most elementary schools in Indonesia, classroom teachers are required to fulfill the dual role of educators and mentors. This study used a qualitative approach with a case study method. Data collection techniques were conducted through observation and in-depth interviews with classroom teachers as key informants. The results indicate that classroom teachers actively implement seven forms of BK services: orientation services, information services, placement and placement, learning, individual counseling, group counseling, and group counseling. Although the implementation does not yet adhere to professional BK service standards, the approach used is contextual and adaptive to the students' circumstances. Classroom teachers play a crucial role in providing guidance through empathetic communication, understanding students' character, and fostering social and emotional values. These findings indicate that empowering classroom teachers in guidance and counseling services has significant potential for creating an inclusive and supportive school environment. This study recommends specialized training for classroom teachers and policy support from schools and the government to strengthen the role of guidance and counseling in elementary schools.